Challenges in Integrated Orthodontic-Periodontic Treatment: A review article - Arwa Al Hugail; Sarah Al-Motlag; Suha Ahmed Alghamdi; Saja Aljumah; Bashaer Mahnashi; Naflah Aldossari; Sharifah Alalwai; Halah Alfaraj; Maryam Boali (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction:As the periodontium is normally affected in adult orthodontic treatment, orthodontics and periodontology are more connected than is true of many other Branches of dentistry. In most of the cases of orthodontic treatment, diagnosis, mid-course periodontal reevaluation, and postorthodontic evaluation, periodontal consideration is mandatory. It can also be useful to remember that periodontal health always influences orthodontic success. Evidenced in the study was that periodontal disease patients require additional treatment from orthodontic tooth movements. Aim of work: To elucidate the orthodontic-periodontic relation for the enhancement of therapy techniques and the attainment of optimal treatment outcomes in patients. Methods: The keywords”interrelationship, orthodontic treatment, periodontal treatment, clinical assessment, orthodontics, periodontics” were used to conduct a thorough literature search in the MEDLINE database in order to find relevant publications published between 2020 and 2024. Using the proper search terms, Google Scholar was utilized to find and access pertinent scientific publications. Various inclusion criteria were used to choose which articles to select. Results: The research included in this study was published from 2017 to 2024. The research included a discussion segment that was broken into many specific elements. Orthodontics and periodontal health are intricately linked. Some areas that are plaque-retenitive may be eliminated using orthodontic. Due to altering life and objectives of individuals, more and more people start to consider having orthodontic treatment. An inter-relationship between orthodontists and periodontists is effective and can improve the planning of the treatment, in a qualitative functional and esthetic manner giving the best possible plans especially in complex case scenarios. Moreover, well developed periodontal surgical procedures such as piezocision and PAOO may augment the movements of orthodontic teeth thus, shortening treatment time of every session. Conclusion: The study’s conclusions highlight the value of an interdisciplinary approach to dental care and call for increased cooperation between periodontists and orthodontists in order to guarantee complete oral health care and maximize treatment outcomes.